2011
DOI: 10.1007/s12013-011-9279-0
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tumor Effects of All-trans Retinoic Acid are Enhanced by Genistein

Abstract: The effects of all-trans retinoic acid (ATRA) on cancer are complex. ATRA has anti-cancer effects as it promotes cancer cell differentiation. However, ATRA also up-regulates expression of vascular endothelial growth factor (VEGF) in cancer cells, which leads to angiogenesis and can, thus, facilitate cancer growth. Genistein, a crucial non-nutrient component in soybean, exhibits anti-cancer effects by inhibiting protein tyrosine kinase that is involved in up-regulation of VEGF. We hypothesized that genistein, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 19 publications
2
15
0
Order By: Relevance
“…Flavonoids are natural occurring polyphenolic compounds with health-prolonging effects such as antioxidant, antitumor and anti-inflammatory properties [4]. Genistein, a soy isoflavone, could enhance anti-cancer effects [5]. There are three hydroxyl groups in molecular structure of genistein in 5, 7 and 4′ positions, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids are natural occurring polyphenolic compounds with health-prolonging effects such as antioxidant, antitumor and anti-inflammatory properties [4]. Genistein, a soy isoflavone, could enhance anti-cancer effects [5]. There are three hydroxyl groups in molecular structure of genistein in 5, 7 and 4′ positions, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…They evaluated the apoptotic effects of 50 µM GEN and 40 µM ATRA on A549 lung adenocarcinoma cells. They showed that when A549 cells were exposed to both compounds, their inhibitory effect was stronger than when each compound used individually (18). Furthermore, in our study there were no significant differences between the cell viability in groups ATRA24 and ATRA48 in comparison with GEN24 and GEN48 that indicates the ability of these two drugs in inhibition of the proliferation in OVCAR-3 cells are somewhat similar.…”
Section: Discussionmentioning
confidence: 99%
“…The role of ATRA in the modification of epigenetic changes in malignancies has been shown in many studies (17). However, the use of ATRA in cancer treatment alone has some limitations (18). It seems that, ATRA in combination with other drugs which modify epigenetic alterations is the appropriate method for the treatment of various cancers including ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of vascular endothelial growth factor was decreased in A549 cells treated with both RA and genistein, indicating that this combination may also hamper the angiogenic process [76].…”
Section: Retinoid and Antiestrogen Synergism: Beyond Breast Cancermentioning
confidence: 99%
“…The phytoestrogen genistein enhanced RA-induced growth inhibition of human lung carcinoma A549 cells by promoting apoptosis and by blocking cell cycle progression in G0/G1 and G2/M phases [76]. The expression of vascular endothelial growth factor was decreased in A549 cells treated with both RA and genistein, indicating that this combination may also hamper the angiogenic process [76].…”
Section: Retinoid and Antiestrogen Synergism: Beyond Breast Cancermentioning
confidence: 99%